Risk assessment of invasive species freshwater crayfish (Cherax quadricarinatus) in Lake Laut Tawar, Aceh - Kasturi Ramdayani; Ali Mashar; Mohammad Mukhlis Kamal; Iwan Hasri (Depik, 2025)
This study aims to assess the distribution of Cherax quadricarinatus based on depth and evaluate its invasiveness using a risk assessment in Lake Laut Tawar, Central Aceh. The study was conducted at five stations representing various lake activities: Station 1 (One-One), Station 2 (Bewang), Station 3 (Gegarang), Station 4 (Mendale), and Station 5 (Dedalu). The methodology involved direct observation in the field followed by laboratory analysis. The results showed that 284 individuals were caught, consisting of 138 females and 146 males, with carapace lengths ranging from 20 to 76 mm. No consistent distribution of male and female carapace lengths was observed across all stations. The abundance of Cherax quadricarinatus in Lake Laut Tawar was classified as very abundant (20%) at One-One and Bewang stations, both at a depth of 5 meters. In conclusion, Cherax quadricarinatus significantly dominates the lake ecosystem, as indicated by its relative abundance at different depths across the study sites. This species also shows a high potential for invasion in freshwater lakes, highlighting the need for effective management strategies.Keywords:Cherax quadricarinatusInvasive spesiesLake Laut Tawar, Aceh